Revisiting the Relationship between Governance Quality and Economic Growth - Salam Ibrahim AlShiab, Mohammad (2020)
This study provides evidence on the relationship between governance quality and economic growth. We use the six Worldwide Governance Indicators (WGI) published by the World Bank and a sample of 29 countries (23 developed countries and 6 emerging economies) covering the period. To account for the potential endogeneity problem, we employ panel GMM estimators. The analysis proceeds in three stages. Firstly, we examine the effect of these six governance indicators on economic growth for the whole sample. Next, we apply a principal component analysis (PCA) to these indicators to construct a global governance index (GGI) and test its impact on economic growth. Finally, to examine the effect of the GGI on economic growth in emerging economies relative to developed countries, we introduce an interaction dummy variable. The results show a positive relationship between governance quality and economic growth in both developed and emerging economies. Moreover, the contribution of the GGI to the economic growth of emerging economies is more than that of developed ones.